Course of hepatitis C virus (HCV) RNA and HCV core antigen testing are predictors for reaching sustained virologic response in liver transplant recipients undergoing sofosbuvir treatment in a real‐life setting. Issue 1 (30th January 2016) - Pischke, S.; Polywka, S.; Proske, V.M.; Lang, M.; Jordan, S.; Nashan, B.; Lohse, A.W.; Sterneck, M.
Abstract: Background: Hepatitis C virus (HCV) infection is associated with reduced graft survival in orthotopic liver transplant recipients. Treatment with the new direct‐acting antivirals (DAAs) is safe and efficient, but no reliable predictive factors for sustained virologic response (SVR) have been identified so far. The HCV core antigen assay (HCV‐core‐Ag) is a new, inexpensive, and efficient method to detect viral antigens, but the value of this technique to predict treatment response in orthotopic liver transplantation (OLT) patients is still unclear. Methods: All OLT patients who were treated with a sofosbuvir‐based antiviral regimen at our center between March 2014 and August 2014 were included in the analysis ( n = 20). HCV‐core‐Ag and HCV RNA (polymerase chain reaction [PCR]) were determined at each visit. Primary endpoints of this study were SVR at 4 or 12 weeks after end of treatment (SVR 4 and SVR 12). Results: HCV‐core‐Ag tested negative after a median of 2 weeks (range 1–16 weeks) while PCR tests became negative after a median of 4 weeks (range 2–12 weeks). Time until PCR negativity and until HCV‐core‐Ag negativity showed a good correlation ( R = 0.711, P < 0.001, Fig. 1 ). Seventeen of 20 patients (85%) achieved SVR 12. SVR 12 was associated with a short time interval between treatment start and HCV PCR negativity ( P = 0.005) or HCV‐core‐Ag negativity ( P = 0.003, Mann–Whitney test). No severe side effects were observed. Conclusions: DAA treatment is safe and well tolerated in OLT. The time points of HCV‐core‐Ag loss and PCR negativity were predictors of SVR 12.